ANALISIS PENGARUH KOMPENSASI DAN LINGKUNGAN KERJA TERHADAP SEMANGAT KERJA KARYAWAN-KARYAWATI PADA PT IRIAN JAYA SEHAT - Reni Junia Akmone; Stepanus Sandy (JEBIMAN : Jurnal Ekonomi, Bisnis, Managemen dan Akuntansi, 2023)
This study aims to determine the effect of compensation and the work environment on the morale of employees at PT. Healthy Irian Jaya. The method used in this research is a quantitative research method, a descriptive research method, namely a research method that describes systematically, factually and accurately about facts, the nature of certain populations or tries to describe phenomena in detail. In this study the techniques used were interviews, case studies and observation. The results of this study indicate that compensation and work environment have a significant influence on morale. The conclusion based on the results of the study shows that companies can pay attention to the factors that affect employee morale, namely compensation and work environment factors so that employees feel comfortable at work to achieve the company's goal of increasing daily turnover